Current Situation and Prospect of Walnut Industry in China - Chen Zhi-Lin; Qi Jian-Xun (SHS Web of Conferences, 2022)
Walnut is one of the four major nuts in the world. China is one of the origins and distribution centers of genus Juglans. Walnut plays an important role in China’s non-wood forest industry, which is of great significance to the national grain and oil security, farmers’ income increase, life quality improvement, and ecological environment construction. On the basis of reviewing the three fields of germplasm resources and breeding, cultivation technologies, and walnut processing and utilization that China’s walnut industry focuses on, this paper puts forward suggestions on the outstanding problems faced by the current industry, in order to provide references for the decision-making of relevant departments.